2018
DOI: 10.7759/cureus.3655
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Quantitative Bone Single Photon Emission Computed Tomography/Computed Tomography for Evaluating Response to Neoadjuvant Chemotherapy in a Patient with Periosteal Osteosarcoma

Abstract: We report here a case of periosteal sarcoma in a 10-year-old female, along with quantitative values obtained with bone single photon emission computed tomography/computed tomography (SPECT/CT), which were useful to evaluate treatment response to preoperative chemotherapy. Pretreatment radiograph images of the lower leg showed cortical thickening eroded by a broad-based soft-tissue mass without the involvement of the underlying cortex, while computed tomography (CT) revealed a small juxtacortical mass with thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This is fundamentally different from traditional nuclear imaging methods, such as planar scintigraphy, SPECT, and nonquantitative SPECT/CT, which use counts per second for their imaging units. With quantitative SPECT/CT, lesion radioactivity can be normalized for injected radioactivity, resulting in quantitative parameter values, such as percent injected dose and SUV [1-3], Quantitative bone SPECT/CT with SUV [4-8], MBV [5, 6], and TBU [5, 6] was subsequently developed following the successful clinical application of SPECT/CT findings in patients with malignant skeletal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is fundamentally different from traditional nuclear imaging methods, such as planar scintigraphy, SPECT, and nonquantitative SPECT/CT, which use counts per second for their imaging units. With quantitative SPECT/CT, lesion radioactivity can be normalized for injected radioactivity, resulting in quantitative parameter values, such as percent injected dose and SUV [1-3], Quantitative bone SPECT/CT with SUV [4-8], MBV [5, 6], and TBU [5, 6] was subsequently developed following the successful clinical application of SPECT/CT findings in patients with malignant skeletal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Two bone SPECT/CT scans using an integrated SPECT/CT system (Discovery NM/CT 670, GE Healthcare) equipped with a low-energy high-resolution collimator were performed 3 h after intravenous injection of 555 MBq of 99m Tc-HMDP. SPECT/CT data were analyzed using a commercially available software package (GI-BONE, Aze Co. Ltd, Tokyo, Japan), which provides statistics for various SUVs, such as the maximum, peak, and mean SUV, as well as the metabolic bone volume (MBV) and total bone uptake (TBU) [6]. The SUVmax was defined as the maximum concentration in the target lesion: (maximum radioactivity/voxel volume)/(injected radioactivity/body weight).…”
Section: Case Reportmentioning
confidence: 99%
“…Kitajima et al 19 reported a case of periosteal sarcoma in a 10-year-old female patient, along with quantitative values obtained with bone SPECT/CT, which were useful to evaluate treatment response to preoperative chemotherapy. Dong et al 20 indicated SUV measurements derived from thyroid SPECT/CT may be useful for the clinical diagnosis and evaluation of Graves' disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although several recently published studies have demonstrated the clinical application of quantitative SPECT/CT for evaluating treatment response in patients with bone disease [5-7], there are no known reports of quantitative SPECT/CT used for evaluating treatment response to bisphosphonates given to PDB patients. Beck et al [5] investigated changes in SUV before and after treatment in 16 breast cancer and 3 prostate cancer patients (hormonal therapy and bisphosphonates) using skeletal quantitative SPECT/CT with 99m Tc-diphosphonopropanedicarboxylic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Umeda et al [6] evaluated the usefulness of three-dimensional TBU for evaluating active bone metastatic burden in 9 prostate cancer patients who underwent Ra-223 therapy and found that the change in TBU derived from the established threshold value (SUV >7.0) was more accurate and sensitive than the change in classic bone scan index in those cases. Furthermore, Kitajima et al [7] reported a case of periosteal osteosarcoma in which SUV max , SUV peak , SUV mean , MBV, and TBU values shown by quantitative bone SPECT/CT were useful to evaluate treatment response to preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%